OP0058 CCR6+ T-cells in children with juvenile idiopathic arthritis. (23rd January 2014) - Sustal, K.N.; Almanzar, G.; Trippen, R.; Höfner, K.; Prelog, M.
Abstract : Background: Previous studies have demonstrated a plasticity of effector-T-cells regarding CCR6 expression in autoimmune disorders. In healthy humans, CCR6+ T-cells have been shown to belong mainly to the Th17 phenotype (characterized by IL-17 production) and CCR6- T-cells to the Th1 phenotype (IFNγ production). Objectives: The present study was aimed to investigate the CCR6+ T-cell phenotype and its plasticity in children with Juvenile idiopathic arthritis (JIA). Methods: Peripheral blood mononuclear cells (PBMCs) of children with JIA (n=25 in clinical remission on medication; n=10 with disease flare) and age-matched healthy donors (HD) (n=21) were analyzed by flowcytometry to assess the phenotype, cytokine production and proliferation of T-cells expressing the chemokine receptor CCR6+. CCR6+ T-cells were separated via magnetic bead isolation. Results: The proportion of CCR6+ T-cells (CD4+ gate) was significantly increased in patients with disease flare (mean 6.3±3.7%) compared to those in remission (3.3±2.7%) or HD (4.0±1.9%) (p<0.05). Regarding the phenotype, almost all CCR6+ T-cells expressed RORgt and CD45RO, but some were CCR7- (77%). Additionally, in JIA patients in remission, about 12.5% of CCR6+ T-cells showed CD161 expression, a marker for the concomitant Th1/Th17 phenotype found in some cases of adult arthritis. CCR6- T-cells were mainly CD45RA+ (50%) and CCR7+ (51.3%), but lost CD161 expression (2.2%). Separated CCR6+ T-cells of JIA patients showed a 17.7-fold higher IL-17 production compared to CCR6- T-cells. However, no significant difference in IFNγ production was determined between CCR6+ or CCR6- T-cell subsets. Conclusions: Our preliminary results confirmed that the CCR6+ T-cell-pool mainly represents the IL-17-producing T-cell subset in JIA patients with disease flare, as well as in remission. Whether CCR6+ T-cells in JIA patients appear to be stable under various cytokine milieus or treatments with biologicals and, thus, offer to be a promising target for future therapies has to be investigated. Disclosure of Interest: None Declared